Interweaving Indonesian Local Wisdoms and Synchronized Virtual Learning: Students’ Experience in ESP - Melania Wiannastiti; Januarius Mujiyanto; Rahayu Puji Haryanti (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2023)
The research delves into integrating Indonesian local wisdom, specifically Pancasila, within synchronized virtual learning for English for Specific Purposes (ESP), aiming to unveil students' experiences and assess the impact on presentation skill development. Thirty students participated in a 13-session Business English presentation course, with Pancasila embedded in the virtual learning mode. Data encompassed closed questionnaires and pretest/post-test scores, analyzed qualitatively and quantitatively. The findings underscore the intervention's efficacy, notably enhancing students' comprehension of Pancasila's cultural significance and augmenting their presentation skills. Notably, improvements were observed in structure, delivery, and gesture, affirming the approach's success in deepening cultural understanding while refining practical abilities. Quantitative analysis revealed shifts in presentation skill scores pre and post-intervention. While medium scores declined, low and high score categories exhibited marked changes, indicative of substantial advancements in presentation proficiency across skill domains. In conclusion, merging Pancasila into synchronized virtual learning yielded notable benefits, aligning cultural content with skill-focused education. This integration not only enriched cultural appreciation but also honed crucial presentation skills. These outcomes accentuate the potential of targeted educational strategies in harmonizing cultural knowledge and skill development within higher education settings, fostering holistic learning experiences. The study advocates for continued exploration and implementation of similar integrative approaches, emphasizing their value in enhancing both cultural understanding and practical skill acquisition among students in specialized learning contexts.